Patient safety at prevention in safe nursing care: Systematic review (Research, Society and Development, 2024)
Several researches related to patient safety have been conducted in recent years, producing discussions about the factors that have correlation or not with risk and falls occurrences in the hospital, being this, one of the problems that threat patient safety. This study aims to identify which advances and practices are being used by the nursing team to reduce the falls risks in the last five years. Therefore, a quantitative and descriptive cross cutting study, performed in systematic review modality, was used without meta-analysis. For the data extraction, a script was created with all the information that should be collected, starting from the PICO method strategy, and the works found were classified in levels of scientific evidence, according to the classification of Melnyk e Fineout- Overholt (2005). It was possible to identify that investigations focus specially in patient’s intrinsic aspects, to indicate as risk factors the occurrence of previous falls, the increased age, vertigo, neurological diseases, medications that act on the Central Nervous System and comorbidities such as Hypertension and Diabetes Mellitus. The studies were predominantly developed in the southern Brazilian region and they used the Morse Fall Scale as the main instrument to evaluation and planning nursing interventions to prevent falls, besides the management of extrinsic factors, such as: raise the bed grids, orient parents about the risk of falls, among others. However, the number of researches that ensures a strong evidence is scarce in national and international literature.